2013
DOI: 10.14257/ijsh.2013.7.6.16
|View full text |Cite
|
Sign up to set email alerts
|

Product Line Pricing Effect Modeling for Shipment Timing Support System for Stored Apple

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In case of micro variable, the researchers used the same independent variables Kwak et al used at aggregate level for excellent grade Fuji apple [6]. We expect that the results from this study can be compared with the results from the Kwak et al's results.…”
Section: Modelingmentioning
confidence: 79%
“…In case of micro variable, the researchers used the same independent variables Kwak et al used at aggregate level for excellent grade Fuji apple [6]. We expect that the results from this study can be compared with the results from the Kwak et al's results.…”
Section: Modelingmentioning
confidence: 79%
“…A price response function model used by Kwak et al, (2011Kwak et al, ( , 2013Kwak et al, ( , 2014 in the STSS for apples is shown in equation (1).…”
Section: Study On Price Response Functions Based On Prospect Theorymentioning
confidence: 99%
“…Dynamic price response function refers to a function that traces the effects of prices in the past, which changes with a time lag, on current or future prices and demand. Therefore, this study conducted modeling by changing the form of equation ( 5) to equation (6) to enable price changes in the past to predict future ones. c2 in equation ( 6) is the non-proportional calculation of the effect of a price increase from the previous period to the present one on prices in the following period.…”
Section: Study On Price Response Functions Based On Prospect Theorymentioning
confidence: 99%
See 2 more Smart Citations